Social psychology - Myers, David G. (McGraw-Hill, 2013)
Introduces students to the science of us; how our thoughts feelings and behaviors are influenced by the world we live in. In this edition, the author is joined by a respected psychology professor and generational differences researcher in presenting an integrated learning program designed for students